2011
DOI: 10.1073/pnas.1016325108
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic and nonergodic processes coexist in the plasma membrane as observed by single-molecule tracking

Abstract: Diffusion in the plasma membrane of living cells is often found to display anomalous dynamics. However, the mechanism underlying this diffusion pattern remains highly controversial. Here, we study the physical mechanism underlying Kv2.1 potassium channel anomalous dynamics using single-molecule tracking. Our analysis includes both time series of individual trajectories and ensemble averages. We show that an ergodic and a nonergodic process coexist in the plasma membrane. The ergodic process resembles a fractal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
708
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(735 citation statements)
references
References 54 publications
22
708
4
1
Order By: Relevance
“…The model discussed in this paper proposes a mechanistic explanation for the nonergodic subdiffusion observed in several biological systems [3][4][5][6][7], based on the occurrence of specific, transient interactions with a heterogeneous population of interacting partners. The model displays many similarities with the long-time behavior of the heavy-tail CTRW [9] and the patch model [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model discussed in this paper proposes a mechanistic explanation for the nonergodic subdiffusion observed in several biological systems [3][4][5][6][7], based on the occurrence of specific, transient interactions with a heterogeneous population of interacting partners. The model displays many similarities with the long-time behavior of the heavy-tail CTRW [9] and the patch model [19].…”
Section: Discussionmentioning
confidence: 99%
“…Such anomalous diffusion can have different physical origins and a large amount of models have been proposed for its interpretation, some of the most relevant ones being recently discussed by Metzler and co-workers [2]. The detailed analysis of the particle trajectories has shown that some processes characterized by anomalous diffusion also exhibit differences between ensemble and time averaged observables, such as the mean squared displacement itself [3][4][5][6][7]. This feature, known as weakergodicity breaking [8], reflects the physical nature of specific stochastic mechanisms, for which time averages are random and thus irreproducible in spite of the large statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the mechanisms in confined geometries that lead to subdiffusive behaviors (corralled, hop, and cage diffusion, as discussed in Fig. S8), mechanisms in ''unconfined'' geometries, such as continuous time random walk (93)(94)(95), fractional Brownian motion (96,97), and random walk on a fractal structure (98), can also give subdiffusive MSD curves (11,41,99). A sophisticated differentiation decision tree, such as the one proposed by Meroz's group (41), should be established and rigorously tested.…”
Section: Challenges In Molecular Trajectory Analysismentioning
confidence: 99%
“…represents the ensemble average, and α > 0 is the exponent which characterizes the diffusion behavior (α < 1, α = 1, and α > 1 correspond to the subdiffusion, normal diffusion, and superdiffusion, respectively). The anomalous behavior is observed in various systems ranging from a charge carrier transport in amorphous material [1], light diffusion [2], polymeric materials [3], to biological transports [4][5][6][7][8][9], The diffusion behavior will depend on the time scale, and thus the exponent α may take several different values depending on ∆. For example, in entangled polymers, the EAMSD of a segment exhibits four different regions which reflect the crossovers between different characteristic relaxation time scales [3].…”
Section: Introductionmentioning
confidence: 99%